Frequency of circulating subpopulations of T‐regulatory cells in patients with hidradenitis suppurativa. (9th December 2019) - Hessam, S.; Gambichler, T.; Höxtermann, S.; Skrygan, M.; Sand, M.; Garcovich, S.; Meyer, T.; Stockfleth, E.; Bechara, F.G.
Abstract: Background: Decreased number of T‐regulatory cells (Tregs) and/or their loss of function potentially lead to uncontrolled immune‐mediated inflammatory responses. There are only few data available on Tregs in hidradenitis suppurativa (HS) – a disease in which it has been suggested that host immune factors and an overactive immune system of the follicular epithelium play a pathogenetic role. Objectives: To analyse frequencies of Tregs subpopulations in blood of HS patients in comparison with a healthy control group. Materials & methods: Blood samples obtained from HS patients and healthy controls were evaluated by flow cytometry and enzyme‐linked immunosorbent assay. Results: The frequency of natural Tregs among CD4+ T lymphocytes were significantly reduced in the HS group compared to the healthy controls. The proportion of activated Tregs, non‐suppressive Tregs and proliferating Tregs showed no significant difference when compared to controls. Regarding Tregs frequencies, there was no significant difference between the three Hurley stages. Serum concentrations of IL‐10, TGF‐ß1 and IL‐17A did not show significant differences between the HS and control group. Conclusion: The reduction of natural Tregs observed in blood of HS patients could be the result of Tregs homing to sites of inflammatory hot spots in HS skin. Further studies are justified evaluating the role of circulating Tregs during the evolution of HS lesions and as a biomarker for treatment response.